2008
DOI: 10.1063/1.2827518
|View full text |Cite
|
Sign up to set email alerts
|

Spectral gap of shear Alfvén waves in a periodic array of magnetic mirrors

Abstract: A multiple magnetic mirror array is formed at the Large Plasma Device (LAPD) [W. Gekelman, H. Pfister, Z. Lucky, J. Bamber, D. Leneman, and J. Maggs, Rev. Sci. Instrum. 62, 2875 (1991)] to study axial periodicity-influenced Alfvén spectra. Shear Alfvén waves (SAW) are launched by antennas inserted in the LAPD plasma and diagnosed by B-dot probes at many axial locations. Alfvén wave spectral gaps and continua are formed similar to wave propagation in other periodic media due to the Bragg effect. The measured wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
76
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(87 citation statements)
references
References 42 publications
11
76
0
Order By: Relevance
“…When a spectrum of Alfvén waves is considered, White et al (2002) demonstrated that the amplitude threshold of the Alfvén waves for ion stochastic heating can be significantly decreased. Evidences of ion heating by low-frequency Alfvén waves have also been found in laboratory experiments (Gates et al 2001;Fredrickson et al 2002;Zhang et al 2008).…”
Section: Introductionmentioning
confidence: 62%
“…When a spectrum of Alfvén waves is considered, White et al (2002) demonstrated that the amplitude threshold of the Alfvén waves for ion stochastic heating can be significantly decreased. Evidences of ion heating by low-frequency Alfvén waves have also been found in laboratory experiments (Gates et al 2001;Fredrickson et al 2002;Zhang et al 2008).…”
Section: Introductionmentioning
confidence: 62%
“…Monochromatic signals or pulses can be applied. It is well known 36,37 that in cylindrical plasmas with a vacuum (or low density) gap between the main plasma and the vacuum vessel, there is the possibility of exciting radial eigenmodes of the fast (compressional) Alfv en wave; however, previous experiments in LAPD using similar antennas in plasmas with either a single ion species, [38][39][40] or two ion species, 30,31 have not observed such modes to be excited in the explored range of frequencies.…”
Section: Methodsmentioning
confidence: 97%
“…A compound antenna consisting of two rectangular current-carrying straps isolated from each other and the plasma 18,19 is inserted into the plasma at the far end of the depletion, 16 m from the plasma source. The antenna is centered on the depletion with the longer current-carrying straps parallel to the background magnetic field B 0 [see Fig.…”
Section: Nonlinear Beat Wave Interaction Among Alfvén Wavesmentioning
confidence: 99%